4‐phenylbutyric acid promotes hepatocellular carcinoma via initiating cancer stem cells through activation of PPAR‐α. Issue 4 (1st May 2021) - Chen, Shu‐Zhen; Ling, Yan; Yu, Le‐Xing; Song, Yu‐Ting; Chen, Xiao‐Fei; Cao, Qi‐Qi; Yu, Han; Chen, Can; Tang, Jiao‐Jiao; Fan, Zhe‐Cai; Miao, Yu‐Shan; Dong, Ya‐Ping; et al.
Abstract: Background and aims: 4‐phenylbutyric acid (4‐PBA) is a low molecular weight fatty acid that is used in clinical practice to treat inherited urea cycle disorders. In previous reports, it acted as a chemical chaperone inhibiting endoplasmic reticulum (ER) stress and unfolded protein response signaling. A few studies have suggested its function against hepatic fibrosis in mice models. However, its role in hepatocarcinogenesis remained unknown. Methods: 4‐PBA was administered alone or in combination with diethylnitrosamine to investigate its long‐term effect on liver tumorigenesis. The role of 4‐PBA in oncogene‐induced hepatocellular carcinoma (HCC) mice model using sleeping beauty system co‐expressed with hMet and β‐catenin point mutation (S45Y) was also observed. RNA‐seq and PCR array were used to screen the pathways and genes involved. In vitro and in vivo studies were conducted to explore the effect of 4‐PBA on liver and validate the underlying mechanism. Results: 4‐PBA alone didn't cause liver tumor in long term. However, it promoted liver tumorigenesis in HCC mice models via initiation of liver cancer stem cells (LCSCs) through Wnt5b‐Fzd5 mediating β‐catenin signaling. Peroxisome proliferator‐activated receptors (PPAR)‐α induced by 4‐PBA was responsible for the activation of β‐catenin signaling. Thus, intervention of PPAR‐α reversed 4‐PBA‐induced initiation of LCSCs and HCC development in vivo . Further study revealed that 4‐PBA could not only upregulate the expression of PPAR‐α transcriptionally but also enhance its stabilization via protecting it from proteolysis. Moreover, high PPAR‐α expression predicted poor prognosis in HCC patients. Conclusions: 4‐PBA could upregulate PPAR‐α to initiate LCSCs by activating β‐catenin signaling pathway, promoting HCC at early stage. Therefore, more discretion should be taken to monitor the potential tumor‐promoting effect of 4‐PBA under HCC‐inducing environment. Abstract : 4‐PBA could promote HCC at early stage of tumor development in vivo . 4‐PBA initiated CSCs via activating Wnt5b‐Fzd5‐β‐catenin signaling pathway dependent of PPAR‐α activation. 4‐PBA could not only regulate the expression of PPAR‐α transcriptionally, but also stabilize it via direct binding.